GALNT6 promotes bladder cancer malignancy and immune escape by epithelial-mesenchymal transition and CD8+ T cells - Sun, Xiaoxin; Wu, Haotian; Tang, Ling; Al-Danakh, Abdullah; Jian, Yuli; Gong, Li; Li, Congchen; Yu, Xiao; Zeng, Guang; Chen, Qiwei; Yang, Deyong; Wang, Shujing (Cancer cell international, 2024)
Bladder cancer (BC) ranks as the sixth cancer in males and the ninth most common cancer worldwide. Conventional treatment modalities, including surgery, radiation, chemotherapy, and immunotherapy, have limited efficacy in certain advanced instances. The involvement of GALNT6-mediated aberrant O-glycosylation modification in several malignancies and immune evasion is a subject of speculation. However, its significance in BC has not been investigated. Through the integration of bioinformatics analysis and laboratory experimentation, we have successfully clarified the role of GALNT6 in BC. Our investigation revealed that GALNT6 has significant expression in BC, and its high expression level correlates with advanced stage and high grade, leading to poor overall survival. Moreover, both in vitro and in vivo experiments demonstrate a strong correlation between elevated levels of GALNT6 and tumor growth, migration, and invasion. Furthermore, there is a negative correlation between elevated GALNT6 levels, the extent of CD8 + T cell infiltration in the tumor microenvironment, and the prognosis of patients. Functional experiments have shown that the increased expression of GALNT6 could enhance the malignant characteristics of cancer cells by activating the epithelial-mesenchymal transition (EMT) pathway. In brief, this study examined the impact of GALNT6-mediated abnormal O-glycosylation on the occurrence and progression of bladder cancer and its influence on immune evasion. It also explored the possible molecular mechanism underlying the interaction between tumor cells and immune cells, as well as the bidirectional signaling involved. These findings offer a novel theoretical foundation rooted in glycobiology for the clinical application of immunotherapy in BC.